Portfolio diversification of residential property investment with gold investment [electronic resource] - Long, Joel Tian Cih, 1989-; Hishamuddin Mohd. Ali, supervisor; Fakulti Geoinformasi dan Harta Tanah (2013)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2013